(untitled) (International Journal of Engineering and Computer Science, 2013)
latest evolutions in GIS technology and spatial information acquisition technology have led to a more distributed data method and computing environment. “Cloud” expertise has appeared as technologies by its focus on large-scale asset sharing and reduced cost for large-scale data storage technology. Specially, the problems of big volume of spatial data in some of the emergency cases which make the needs for elastic way for storing and analysis and computing all of these resources. In this paper we proposed an architecture for spatial data processing based on cloud computing technology. The results showed better performance in comparison to previous works